The Youth Party-Subculture: A Prerequisite for Adulthood Success? - Mills, Mollie V (2011)
Research has not yet examined the relationship between minor teenage deviance and later adulthood success. Building on previous research by Moffitt (1993) and Hagan’s (1991) youth party-subculture, I will define and compare four adolescent groups based on offending type. I argue that minor deviance, rooted in the party-subculture, will enhance social and networking skills that will be beneficial in adulthood. College attainment, serving as a social control, is expected to moderate the effects of deviance, benefiting party-subculture youth. Using the National Longitudinal Study of Adolescent Health dataset, findings suggest that adolescents engaging in minor deviance are more extroverted in adulthood, with little difference in earnings when compared to party-subculture abstainers. However, adolescent deviants continue substance use and deviance into adulthood significantly more than party-subculture abstainers